Soliton collision and crosstalk management using a micro-ring resonator System - Tadee, K.; Threepak, T.; Mitatha, S.; Bunyatnoparat, P.; Yupapin, P. P. (My University, 2009)
We present the interesting system that consists of a micro ring resonator system incorporating an add/drop filter. By using the appropriate parameters relating to the practical device. we found that the obtained multisolitons can be benefit the dense wavelength division multiplexing application, whereas the different center wavelengths of the soliton bands can be obtained via the add/drop filter without the collision, which can be used to increase the communication channel capacity in communication network. ©2009 IEEE.